Crystal structure of (4-fluorobenzyl)triphenylphosphonium bromide, C25H21BrFP - Liu Shuxin; Tian Xinyao; Qiu Zilong; Li Liguo; Li Xiuhua (Zeitschrift für Kristallographie - New Crystal Structures)
C25H21BrFP, monoclinic, P21/n (no. 14), a = 9.6550(2) Å, b = 14.0446(3) Å, c = 16.0765(2) Å, β = 99.634(1)∘, V = 2149.24(7) Å3, Z = 4, Rgt (F) = 0.0425, wRref (F2) = 0.1162, T = 301.5(10) K.